Phosphorus Recovery from Phosphate Rocks Using Phosphate-Solubilizing Bacteria. Issue 3 (16th March 2019) - do Carmo, Taciana S.; Moreira, Felipe S.; Cabral, Bruna V.; Dantas, Raquel C. C.; de Resende, Miriam M.; Cardoso, Vicelma L.; Ribeiro, Eloízio J.
Abstract: In this paper, we are presenting a biological process to recover phosphorus by solubilizing low-grade phosphate rocks. To this end, the efficiency of different phosphate-solubilizing microorganism (PSM) species for solubilizing P from phosphate rocks using both pure cultures and associations. Nutritional conditions, phosphate rock concentrations, and reactor designs were tested. The genus Bacillus, especially Bacillus megaterium (ATCC 14581), was found to be the most promising PSM for solubilizing P. Production of organic acids and acidic pH values were shown to be directly related to P solubilizing. However, associations between tested microorganisms did not significantly enhance process efficiency. We conclude that nutritional factors of the medium are important to solubilization, and lower phosphate rock concentrations lead to better solubilization. The Air Lift reactor was promising for B. megaterium (ATCC 14581), but adaptations are needed for further tests.